Disillusioned : five families and the unraveling of America's suburbs - Herold, Benjamin (Penguin Press, 2024)
"Through the stories of five American families, a masterful and timely exploration of how hope, history, and racial denial collide in the suburbs and their schools Outside Atlanta, a middle-class Black family faces off with a school system seemingly bent on punishing their teenage son. North of Dallas, a conservative white family relocates to an affluent suburban enclave, but can't escape the changes sweeping the country. On Chicago's North Shore, a multiracial mom throws herself into an ultra-progressive challenge to the town's liberal status quo. In Compton, California, whose suburban roots are now barely recognizable, undocumented Hispanic parents place their gifted son's future in the hands of educators at a remarkable elementary school. And outside Pittsburgh, a Black mother buys a home on the same street where the author grew up, then confronts the destructive legacy left behind by white families like his. Education journalist Benjamin Herold's ability to braid these compelling human stories together with local and national history makes Disillusioned an astonishing reading experience, along with an urgent argument that America's suburbs and their schools are locked into a destructive cycle that has brought the country to a point of crisis. For generations, white families have reaped the benefits of massive federal investment in suburbia, then moved on as social and political infrastructure began to fail, leaving the mostly Black and brown families who follow to clean up the ensuing mess. Now, though, the suburbs are caught between rapidly shifting demographics and the reality that endless expansion is no longer feasible. Forced to confront truths that their communities were built to avoid, everyday suburban families find themselves at the center of the nation's most pressing debates: How do we repair America's divided communities? How do we build a future for all our children? In exploring these questions, Herold pulls back the curtain on suburban public schools and school boards, which he persuasively argues are the new ground zero in the fight for the country's future. Herold brings together research on the effects of racism on everyone with empathetic portrayals of families of wildly different backgrounds and perspectives. Nothing short of a journalistic masterpiece, Disillusioned brings readers face-to-face with the roots of America's discontent. Then, alongside the Black mother from his old neighborhood, who contributes a powerful epilogue to the book, Herold offers a hopeful path toward renewal"--